Pengembangan Video INSAN untuk Meningkatkan Motivasi Pembelajaran PAI Siswa di Sekolah Dasar - Zehanara, Nelyan Setia; Tsany, Marlinda Salwa Talitha; Setiawati, Tina; Aeni, Ani Nur (Mitra PGMI: Jurnal Kependidikan MI, 2024)
Islamic Religious Education (PAI) learning can be used as an effort to foster an attitude of respect for diversity from an early age. However, students' learning motivation in PAI learning is still low, mainly due to the dominant and teacher-centered lecture method. This study aims to examine the effectiveness of INSAN (The Beauty of Mutual Respect in Diversity) animated video in increasing students' learning motivation in PAI learning. The research method used is Design and Development (D&D) with the ADDIE development model. The data was collected using a questionnaire and the feasibility test was conducted on 19 fourth grade students of SDN Sukanagara, Sumedang. The validation results showed that the INSAN animated video obtained an average percentage of 90.0% (very feasible) from media experts and 84.9% (very feasible) from material experts. The student response questionnaire showed an average percentage of 88.3%, which indicates a very positive response and high feasibility. In conclusion, the INSAN animated video is effective in increasing motivation to learn PAI and developing mutual respect in diversity.